1990
DOI: 10.1007/bf00146546
|View full text |Cite
|
Sign up to set email alerts
|

Steady-state pattern electroretinogram following long term unilateral administration of timolol to ocular hypertensive subjects

Abstract: To determine whether long-term reduction of intraocular pressure leads to a corresponding preservation of the pattern electroretinogram (PERG), PERGs were studied in 21 patients with ocular hypertension who had received unilateral timolol therapy for a minimum of 6 years. The mean difference in intraocular pressure (IOP) between the placebo-treated and the timolol-treated eyes (over 6 years) was 2.4 mm Hg. Steady-state PERGs (16.0 rps) were obtained simultaneously in both eyes of each patient, with four check … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 15 publications
1
13
1
Order By: Relevance
“…Tak en together, these findings indicate that the degree and prevalence of pattern electroreti nogram abnormalities in treated ocular hyper tension are associated with the individual in traocular pressure control in the 15-25 mm Hg range. The present results confirm pre vious data on treated ocular hypertensives [14,15], and show, in addition, that timololtreated eyes with moderate hypertension ex hibit pattern electroretinogram losses that are comparable to those of untreated eyes retain ing similar intraocular pressures. The differ ences in pattern electroretinogram ampli tudes across ocular hypertensives found in the present study may presumably reflect differ ent degrees of ganglion cell dysfunction asso ciated with long-term intraocular pressure control.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Tak en together, these findings indicate that the degree and prevalence of pattern electroreti nogram abnormalities in treated ocular hyper tension are associated with the individual in traocular pressure control in the 15-25 mm Hg range. The present results confirm pre vious data on treated ocular hypertensives [14,15], and show, in addition, that timololtreated eyes with moderate hypertension ex hibit pattern electroretinogram losses that are comparable to those of untreated eyes retain ing similar intraocular pressures. The differ ences in pattern electroretinogram ampli tudes across ocular hypertensives found in the present study may presumably reflect differ ent degrees of ganglion cell dysfunction asso ciated with long-term intraocular pressure control.…”
Section: Discussionsupporting
confidence: 90%
“…The results of two recent prospective studies have indicated that in traocular pressure normalization can prevent or delay the onset of visual field damage in treated as compared to untreated ocular hy pertensive eyes [10], or prevents the progres sion of visual field defects in eyes with early glaucoma [11], The relationship between pat tern electroretinogram changes and intraocu lar pressure control in treated ocular hyper tension is currently a matter of investigation. In a cross-sectional study on patients with moderate ocular hypertension who had re ceived unilateral long-term treatment with ti molol (and a placebo in the fellow eye), Nesher et al [14] reported no significant differ ences in the electroretinographic amplitudes between the timolol-treated and placebotreated eyes, or between hypertensive eyes (either timolol or placebo treated) and normal controls. However, the authors showed in a correlational analysis that amplitudes tended to be lower in eyes with higher intraocular pressures.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous reports of early PERG impairment in glaucoma, 56,57 optic nerve diseases, 58 and diabetes 59,60 at least in part may be due to altered axon transport. Also, recovery of PERG amplitude losses after either IOP lowering 15,17,18,61,62 or removal of pituitary tumors 63 may be related to restoration of axon transport. Thus, the PERG may represent a promising marker of early, reversible axonal dysfunction preceding RGC death in glaucoma and optic nerve diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the observed correlation between high IOP and reduced PERG response, likely as a result of RGC dysfunction, Feghali et al demonstrated that, in rabbits with low PERG amplitude associated with high IOP, the amplitude was immediately normalized when the IOP was lowered (57) . Other studies have evaluated the effect of medically or surgically reduced IOP on PERG response in humans (58)(59)(60) . After following OHT patients treated with timolol as well as a control group receiving placebo for six years, Nesher et al observed a significant correlation between IOP levels and steady-state PERG amplitude (58) .…”
Section: Abnormalities In Perg Amplitudementioning
confidence: 99%
“…Other studies have evaluated the effect of medically or surgically reduced IOP on PERG response in humans (58)(59)(60) . After following OHT patients treated with timolol as well as a control group receiving placebo for six years, Nesher et al observed a significant correlation between IOP levels and steady-state PERG amplitude (58) . Spadea et al observed no recovery of the PERG amplitude trabaculectomy was performed on eyes with advanced glaucoma (59) ; however, other authors reported that the PERG response could be restored after pharmacologically induced IOP reduction in low-and high-tension glaucomatous eyes, even in the presence of early VF de fects (60) , suggesting that PERG reduction is related not only to RGC loss, but also to RGC dysfunction.…”
Section: Abnormalities In Perg Amplitudementioning
confidence: 99%